2015
DOI: 10.1007/s11661-015-3221-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Susceptibility of Nanostructured Bainitic Steels

Abstract: Nanostructured steels with an ultimate tensile strength of 1.6 GPa were produced with austenite content varying from 0 to 35 vol pct. The effect on the mechanical properties was assessed after saturating the steel with hydrogen. Elongation was reduced to 2 to 5 pct and UTS to 65 to 70 pct of prior value. Thermal desorption measurements confirmed the higher solubility of hydrogen in the steel with higher austenite content. The level of hydrogen saturation was found to correlate to the total area of grain bounda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Peet and Hojo [7] have conducted thermal desorption experiments in nanostructured bainitic steels, including one tempered at 500 °C. In the sample asisothermally transformed with 35.1% retained austenite the amount of hydrogen desorbed was 7.1 ppmw, but in the tempered sample (without retained austenite) the amount of hydrogen desorbed was 3.0 ppmw.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Peet and Hojo [7] have conducted thermal desorption experiments in nanostructured bainitic steels, including one tempered at 500 °C. In the sample asisothermally transformed with 35.1% retained austenite the amount of hydrogen desorbed was 7.1 ppmw, but in the tempered sample (without retained austenite) the amount of hydrogen desorbed was 3.0 ppmw.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on hydrogen in nanostructured bainite have suggested that the level of hydrogen saturation is correlated to the total area of α/γ interfaces per unit volume rather than to the volume fraction of retained austenite [7,21]. However, this result does not account for the conflicting values of retained austenite after isothermal transformation [21] or assumptions in bainitic ferrite plate width that affect the estimation of surface area per unit volume of the α/γ interfaces [7].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, NiP-3 coated steel showed a higher increase in the YS than NiP-1 coated steel after H-charging, even though the NiP-3 coating is of a higher thickness (5.5 µm) compared to NiP-1 coating (3.5 µm). A HES study of three different high-strength steels by Peet and Hojo [40] reported that the effect of H-charging on the HES can be well perceived by comparing the %EL values for H-charged and uncharged conditions (Table II in Ref [40]).…”
Section: Resistance To Hydrogen Embrittlementmentioning
confidence: 99%